Athletes first? The right to health and safety in postponing the Tokyo Olympic Games - Xiao, H. (Human Rights Defender, 2020)
Indeed, the Olympic and Paralympic movement itself is meant to serve and be an inspiration to society. Yet in recent years, we have seen large movements against the hosting of the Games in many cities, suggesting that not all of society believes in the unifying power of the movement`s ultimate event. Most recently, the coronavirus pandemic has put the IOC`s ethics and ideals to the test. It highlighted several issues with the IOC`s priorities and the power dynamics within the organisation.